Physical and emotional health among nurses in protracted crisis settings in Lebanon and Jordan: A cross-sectional study - Nuhad Dumit; Gladys Honein-AbouHaidar; Muntaha K. Gharaibeh; Ibtisam M. Al-Zaru; Reem Hoteit; Imad Bou-Hamad; Patricia Davidson; Nancy Reynolds (PLoS ONE, 2026)
Objectives Nurses working in crisis-affected and refugee-hosting settings face demanding conditions that may compromise their physical and emotional health. Evidence on the prevalence and determinants of these outcomes in such contexts remains limited. This study assessed nurses’ physical and emotional health in Lebanon and Jordan and identified key associated factors using regression and random forest models. Methods A cross-sectional survey was conducted among hospital nurses providing care to Syrian refugees in Lebanon (n = 976; response rate 52%) and Jordan (n = 2,012; response rate 80.5%). Back pain, general weakness and emotional exhaustion outcomes were assessed alongside sociodemographic, work-related, and psychosocial work variables. Logistic, linear regression and random forest models were performed on merged and country-specific datasets. Results Nearly six in ten nurses in Lebanon and more than seven in ten in Jordan reported strong general weakness, and over 60% in both countries experienced strong back pain. Emotional exhaustion was prevalent and higher among Jordanian nurses (4.13, SD = 1.39) compared to Lebanese nurses (3.49, SD = 1.70). Age, gender, working hours, and work unit were significant demographic and occupational predictors, while job conflict, self-perceived workload, lack of job preparation, and workload stress emerged as important work environment factors. Nursing resources and teamwork were consistently protective. Random forest models confirmed the relative importance of workload-related factors and highlighted the close association between physical health and emotional exhaustion. Conclusion Hospital nurses caring for refugees in Lebanon and Jordan experience high levels of physical and emotional health strains associated with workload, work unit, psychosocial strain, and organizational resources. Findings highlight the need for system-level workforce policies, including workload regulation, staffing optimization, and strengthened organizational support to promote nurse well-being and enhance health system resilience in refugee-hosting and resource-constrained settings.